The relationship between anxiety levels and hypertension among older adults - Jita Gabela; Suryani Suryani; Zubaida Rohmawati (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Hypertension is known as the silent killer because it often does not cause specific complaints or symptoms. Normally, a person's blood pressure ranges from 100-140 mmHg systolic and 60-90 mmHg diastolic. Blood pressure is not only influenced by physical factors, but also psychological conditions. Anxiety is one psychological aspect that is closely related to hypertension. The prevalence of hypertension in Yogyakarta was highest in 2022 at 28.420 cases and lowest in 2018 (18.057 people). Purpose: To determine the relationship between anxiety levels and hypertension among older adults. Method: A quantitative research design with an analytical observation method and a cross-sectional approach on 75 elderly people suffering from hypertension using total sampling. The measurement tools used to collect data on anxiety levels were the GAI questionnaire and blood pressure measurements using a digital sphygmomanometer. The data analysis used was univariate and bivariate analysis. Bivariate analysis used Kendall's tau test. Results: The results showed that 53.3% of respondents had stage 2 hypertension, and 60% of them experienced severe anxiety. The bivariate test on the variable of anxiety level with the incidence of hypertension was p value = 0.001 with a significance level of α = 0.05, which means that there is a significant relationship between anxiety level and the incidence of hypertension in the elderly. Conclusion: There is a relationship between anxiety levels and the incidence of hypertension in the older adults. Keywords: Anxiety; Blood Pressure; Elderly; Hypertension.